(1314) economies of scale in the Egyptian industry-the case of steel and fertilizers - nassef, el sayed (the institute of national planning, 2018)
the aim of this paper is to apply the concept of economies of scale to the Egyptian industry. three activities were selected: textiles, steel,and fertilizers. for these same industrial activities, we have tried, in a previews paper, to identify the relationship between wages, productivity, and cost of living.